2004
DOI: 10.2527/2004.82113288x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer visual preference and value for beef steaks differing in marbling level and color1

Abstract: ABSTRACT:To determine visual preference and value for fresh beef steaks differing in marbling level and color, consumers in Chicago and San Francisco (n = 124 per city) evaluated two pairs of steaks in a retail case. Steaks differing in marbling level (Modest/ Moderate vs. Slight) and color (bright, cherry-red vs. dark red) were purchased at retail stores in each city. Consumers selected their preferred steak in each pair, described their selection criteria, and provided the price they were willing to pay for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
1
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(62 citation statements)
references
References 9 publications
3
51
1
7
Order By: Relevance
“…When compared to prior studies using consumer visual panels, the results of the current study differ from those previously reported (Killinger et al, 2004;Claborn et al, 2011;DeVuyst et al, 2014). Killinger et al (2004) reported consumers were willing to pay more for steaks with a low level of marbling and bright cherry-red color in comparison to those with high levels of marbling and similar color. Similarly, Claborn et al (2011) reported consumer preference towards reduced marbling levels when purchasing steaks.…”
Section: Quality Gradecontrasting
confidence: 56%
“…When compared to prior studies using consumer visual panels, the results of the current study differ from those previously reported (Killinger et al, 2004;Claborn et al, 2011;DeVuyst et al, 2014). Killinger et al (2004) reported consumers were willing to pay more for steaks with a low level of marbling and bright cherry-red color in comparison to those with high levels of marbling and similar color. Similarly, Claborn et al (2011) reported consumer preference towards reduced marbling levels when purchasing steaks.…”
Section: Quality Gradecontrasting
confidence: 56%
“…Analyzing the results of the consumer assessment, it can be seen that the most attractive meat colors were bright red and cherry red. Similar meat color preferences have been shown for consumers in the Unated States and Germany (Killinger et al, 2004;Grebitus et al, 2013).…”
Section: Consumer Assessmentmentioning
confidence: 63%
“…Because steaks from the visual evaluation (Killinger et al, 2004) were visible during the practice auctions, it was decided that those steaks should be used as the products for the first two practice auctions. For the first practice auction, the consumers were told that they would be bidding on a 0.45-kg package of steak similar to one of the visual evaluation steaks.…”
Section: Practice Auctionsmentioning
confidence: 99%